Assessment of wound healing potential of copper (II) Bis [N'-((5-chloro-1H-indol-3-YL) methylene) nicotinohydrazide] on experimentally-induced excision wounds in rats - Rahnama, M.; Salama, S.M.; Majid, N.A.; Darvish, P.H.; Golbabapour, S.; Aziz, P.Y.; Gwaram, N.S.; Salehen, N.; Abdulla, M.A. (Hindawi Publishing Corporation, 2014)
Copper (II) Schiff base derivatives are frequently used for the treatment of many disorders. The aim of current study was to investigate the effects of the Schiff base derivatives on rats of wound healing enclosure and histology of granulation tissues in rats. Wound healing activity of Copper (II) Bis [N'-((5-chloro-1H-indol-3-YL) methylene) nicotinohydrazide] which is shortly called CI-indole-nicotinic, was perused by specifing the percentage of wound closure after tropical application of the compound. Four groups of animals were treated respectively with 0.2mL of gum acacia, 0.2mL of Intrasite gel, 0.2mL of CI-indole-nicotinic (50 mg/mL) and 0.2mL of CI-indole-nicotinic (100 mg/mL) for 10 days to assess the gross rate of wound enclosure, histology and endogenous enzymes parameters. The results indicated the affective capacity of CI-indole-nicotinic inj tissue regenetration and healing the injured skin. Grossing on day 5 and day 10 declared that the compound significantly accelerated the rate of wound healing. Histology of granulation tissues indicated remarkably the angiogenesis augmentation and increased fibroblasts and collagen formation as well as reduction in flammatory cells balance in CI-indole-nicotinic-treated groups compared to control group. Moreover, the compund represented dose-dependent levels of superoxide dismutase (SOD) and slight lipid peroxidation enzyme - malondialdedhyde (MDA) inhibition in granulation tissue. The acute toxity examination displayed no nephorotoxic or hepatotoxic side effects. In conclusion, wound healing capability of CI-indole-nicotinic compund could possibly attribute to enhance collagen deposition in granulation tissue and antioxidant activity of the compound.